Electronic Health Record Portal Adoption - Tavares, Jorge (2017)
Tavares, J., & Oliveira, T. (2017). Electronic Health Record Portal Adoption: A cross country analysis. BMC Medical Informatics and Decision Making, 17(1), [97]. https://doi.org/10.1186/s12911-017-0482-9